2020
DOI: 10.1136/bmjgh-2020-003493
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial evaluation of trade-offs between equity in physical access to healthcare and health systems efficiency

Abstract: IntroductionDecisions regarding the geographical placement of healthcare services require consideration of trade-offs between equity and efficiency, but few empirical assessments are available. We applied a novel geospatial framework to study these trade-offs in four African countries.MethodsGeolocation data on population density (a surrogate for efficiency), health centres and cancer referral centres in Kenya, Malawi, Tanzania and Rwanda were obtained from online databases. Travel time to the closest facility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…If a patient does not have access to facilities, then they would not have access to the diagnostics. As an example, Namibia has poor accessibility to facilities (in terms of access within 2 h for the population), 25 but high availability of diagnostics at the facilities. This study also did not evaluate the number of tests performed or whether skilled staff were available, only that there was functioning equipment.…”
Section: Discussionmentioning
confidence: 99%
“…If a patient does not have access to facilities, then they would not have access to the diagnostics. As an example, Namibia has poor accessibility to facilities (in terms of access within 2 h for the population), 25 but high availability of diagnostics at the facilities. This study also did not evaluate the number of tests performed or whether skilled staff were available, only that there was functioning equipment.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, Alhassan et al [27] reported that health facilities located in rural parts of western Ghana had higher odds (42.9-52.1%) of being efficient, as compared to those in the capital city (p = 0.002). In a recent study to evaluate the trade-offs between geospatial equity and health systems efficiency in Kenya, Malawi, Tanzania, and Rwanda, Iyer et al [36] found evidence to suggest that in prioritising efficiency, considerate choices with regard to geographical allocation of health resources could enhance equitable physical access to services.…”
Section: Empirical Examples Of Equity and Efficiency Considerations In Healthcarementioning
confidence: 99%
“…This implies that such targets are easily attainable within the geographic extent of our study area. Scaling back to this degree however poses concerns regarding equity of access [ 48 ]. For a disease like g-HAT, which predominantly affects rural populations, severe scaling back to achieve moderate targets could leave remote communities without coverage.…”
Section: Discussionmentioning
confidence: 99%